1997
DOI: 10.1177/074193259701800406
|View full text |Cite
|
Sign up to set email alerts
|

A Team-Based Junior High Inclusion Program

Abstract: Parent perceptions and attitudes regarding the inclusion of students with mild to moderate disabilities into general classrooms have been mixed. In this qualitative study, the parents of 17 students with learning disabilities and 1 student with behavior disorders were interviewed following the first year of a junior high inclusion pilot program based on teacher and student collaborative teams. Twelve response categories are identified. Parents recognized personal attention for students and positive attributes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…To address the individual needs of students, parents in this study, as in other studies (Bowen, 1998;Gibb & Young, 1997;Love, 1996), identified the need for greater (a) parent and teacher communication, and (b) teacher and student communication.…”
Section: Addressing Individual Student Needsmentioning
confidence: 67%
“…To address the individual needs of students, parents in this study, as in other studies (Bowen, 1998;Gibb & Young, 1997;Love, 1996), identified the need for greater (a) parent and teacher communication, and (b) teacher and student communication.…”
Section: Addressing Individual Student Needsmentioning
confidence: 67%
“…Understandably, for parents, positive attitudes about inclusion appeared to be the norm, although anxiety about the actual mechanics of inclusion has also been reported (Bennett, DeLuca, & Bruns, 1997;Gibb et al, 1997). This ambiguity was clearly seen among parents who supported inclusion but had reservations about it for their children (Lovitt et al, 1999).…”
Section: Attitudesmentioning
confidence: 69%
“…Through this type of analysis, the findings were firmly &dquo;grounded&dquo; in the data, as opposed to predetermined assumptions I could have brought to the research focus (Glaser & Strauss, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…In recruiting participants, I used a process of &dquo;purposeful sampling&dquo; whereby I sought out parents who would add a dimension to the data that might not appear otherwise (Glaser & Strauss, 1967). I attempted to &dquo;consciously vary the type of people interviewed&dquo; (Taylor & Bogdan, 1984, p. 83).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation